Applying the Concept of Successful Aging to Thailand - Pekalee, Alongkorn; Ingersoll-Dayton, Berit; Gray, Rossarin Soottipong; Rittirong, Jongjit; Völker, Marc (Journal of Population and Social Studies [JPSS], 2020)
Objectives: This research aims to examine the components of Rowe and Kahn’s model of successful aging as applied to the Thai population who are categorized as: young-old (60-69), old-old (70-79), and oldest-old (80 and over). Method: The study is based on the Survey of Older Persons in Thailand of the National Statistical Office, 2011 (n = 24,433). Confirmatory Factor Analysis is used to test whether Rowe and Kahn’s model, which comprises three domains - avoiding disease and disability, maintaining physical and cognitive functioning, and continuing engagement with life, is confirmed by these data. Multiple group analysis is performed to determine factor loading differences among age groups. Results: Rowe and Kahn’s model has a good statistical fit when applied to data of the current study. Factor loadings for three age groups is statistically different (p<0.001). Of the three domains, continuing engagement with life is the domain most strongly associated with successful aging, particularly among the old-old and the oldest-old. Implications: Programs to support health and social engagement should be promoted and enhancing active engagement should be a priority since older Thai people have low levels of social participation.